Gill Infection Model for Columnaris Disease in Common Carp and Rainbow Trout. Issue 1 (8th December 2014) - Declercq, A. M.; Chiers, K.; Haesebrouck, F.; Van den Broeck, W.; Dewulf, J.; Cornelissen, M.; Decostere, A.
Abstract: Challenge models generating gill lesions typical for columnaris disease were developed for the fry of both Common Carp Cyprinus carpio and Rainbow Trout Oncorhynchus mykiss by means of an immersion challenge and Flavobacterium columnare field isolates were characterized regarding virulence. Carp inoculated with highly virulent isolates revealed diffuse, whitish discoloration of the gills affecting all arches, while in trout mostly unilateral focal lesions, which were restricted to the first two gill arches, occurred. Light microscopic examination of the gills of carp exposed to highly virulent isolates revealed a diffuse loss of branchial structures and desquamation and necrosis of gill epithelium with fusion of filaments and lamellae. In severe cases, large parts of the filaments were replaced with necrotic debris entangled with massive clusters of F. columnare bacterial cells enwrapped in an eosinophilic matrix. In trout, histopathologic lesions were similar but less extensive and much more focal, and well delineated from apparently healthy tissue. Scanning and transmission electron microscopic observations of the affected gills showed long, slender bacterial cells contained in an extracellular matrix and in close contact with the destructed gill tissue. This is the first study to reveal gill lesions typical for columnaris disease at macroscopic, light microscopic, and ultrastructural levels in both Common Carp and Rainbow Trout following a challenge with F. columnare . The results provide a basis for research opportunities to examine pathogen–gill interactions. Received January 10, 2014; accepted July 27, 2014